PENETRATION TESTING TERHADAP DAMNVULNERABLE WEB APPLICATION (DVWA) MENGGUNAKAN METODE ZERO ENTRY HACKING (ZEH) DAN OPEN WEB APPLICATION SECURITY PROJECT (OWASP) - Leonardo Pandapotan (2021)
This study aims to test vulnerabilities to determine the security condition of the DVWA web application and describe the gaps found because information security systems are very important with advances in information technology and also to help the needs of the people who use them. The penetration testing (pentest) methodology used in this study is Zero Entry Hacking (ZEH) which has 4 (four) stages, namely Reconnaissance, Scanning, Exploitation, and Post Exploitation and Maintenance Access and takes solutions from the Open Web Application Security Project (OWASP). . The results obtained from the scanning process are in the form of warnings and vulnerabilities as well as knowing the condition of the security level of the DVWA web application system by exploiting cross-site scripting (XSS), command injection, file inclusion, file uploading, brute force attacks, and SQL injection along with solutions from Open the Web Application Security Project (OWASP).